Analisis Potensi Wisata Olahraga Paralayang di Bukit Lelato Desa Lomuli Kecamatan Lemito Kabupaten Pohuwato - Gui, Jamaludin Bahtiar; Rahayu, Tandiyo; Setyawati, Heny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This research aims to analyze the potential for paragliding tourism on Lelato Hill based on Standard Operating Procedures, analyzing what obstacles there are to paragliding tourism on Lelato Hill, Lomuli Village, Lemito District, Pohuwato Regency, analyzing the management of paragliding tourism on Lelato Hill, Lomuli Village, Lemito District, Pohuwato Regency. This research uses a qualitative descriptive approach with a case study design because it tries to understand the phenomenon and does not try to manipulate the observed phenomena. Data collection was carried out using interviews, observation, and documentation. Data and data sources come from primary data and secondary data. The research results show potential for paragliding tourism on Lelato Hill. The development of parachute sports has resulted in an unhindered and vertical flight of 16 degrees, an open landing area, and natural conditions that can be seen from the paragliding track. It's a track, but the weather is cloudy. Meanwhile, weather and wind conditions, 30-day average, 14.5 km/h. The obstacles to paragliding tourism in the form of community resources are that paragliding has not yet realized its potential as sports tourism, road access is still overland, and pilots are still at the single pilot license level. Parachute equipment, reserve parachute, anemometer, etc. The management is a tourism awareness group that manages paragliding tourism. The conclusion is that Lellato Hill can be used as a paragliding tourism location if it has adequate take-off and landing facilities and meets the required standards. Natural conditions such as weather and wind are also very favorable at certain times. This is an opportunity to make Lelato Hill a major paragliding tourism destination. Keywords: Tourism Potential, Standard Operating Procedures, Lelato Hill